Towards a new national forest classification for South Africa - Mucina, Ladislav; Geldenhuys, C. (2006)
The indigenous mixed evergreen forests of South Africa were classified to define forest types at the national level as a basis for policy development and to conserve biodiversity. The forests are generally small and occur in a fragmented zone along the eastern side of the country, mainly along the eastern escarpment and mountain ranges, but also along the Indian Ocean coast. About 4500 releves from many different published and unpublished vegetation studies were used. Most data used are based on stems by species and stem diameter on 400 m2 plots. Some data sets included all higher plant species, some of which were recorded by cover-abundance values. The vegetation data were subject to computer-assisted formalized classification and ordination procedures to delimit the major forest types and to define their position along major environmental gradients. A series of iterative steps involving global TWINSPAN analyses (including all releves), and local analyses (limited to part of the handled table) were performed. A total of eight Forest Groups and 24 Forest Types were identified and described.